Greenhouse gas emission of biogas production out of silage maize and sugar beet – An assessment along the entire production chain. (15th March 2017) - Jacobs, Anna; Auburger, Sebastian; Bahrs, Enno; Brauer-Siebrecht, Wiebke; Christen, Olaf; Götze, Philipp; Koch, Heinz-Josef; Rücknagel, Jan; Märländer, Bernward
Highlights: GHG-emission, bioenergy yield, GHG-saving potential based on field trial data. Results complement the absence of default values, especially for sugar beet. Results represent Central European conditions of crop and biogas production. Abstract: The study delivers values on greenhouse gas (GHG)-emission via cultivation of silage maize and sugar beet and of GHG-saving potential of electricity produced from biogas out of both biomass crops. Data are based on three rainfed crop rotation field trials in Germany (2011–2014) representative for Central Europe and can serve as default values. It was found that GHG-emission via crop cultivation was driven mainly by nitrous oxide emission from soil and mineral N-fertilizer use and was 2575–3390 kg carbon dioxide equivalents (CO2 eq) per hectare for silage maize and 2551–2852 kg CO2 eq ha −1 for sugar beet (without biogas digestate application). Integrating a GHG-credit for surplus N in the biogas digestate reduced total GHG-emission via crop cultivation to 65–69% for silage maize but only to 84–97% for sugar beet. The GHG-saving potential of electricity production from biogas was calculated for three biogas plants differing in technical characteristics. The GHG-saving potentials were generally >70% (silage maize: 78–80%, sugar beet: 72–76%) and the authors concluded that the technical setting of the biogas plant had a slight impact only. Overall, the authors assumed that the major potential for GHG-emission's reduction along the bioenergy production chain were N-management during crop cultivation and methane losses at the biogas plant. Finally, sugar beet, if cultivated in crop rotation, was shown to be an efficient alternative to silage maize as a biomass crop in order to achieve a higher diversity in biomass crop cultivation.